Physical Exercise for Older People with Hypertension in COVID-19 Pandemic: A Literature Review - Ni Luh Putu Dian Yunita Sari; I Kadek Prastikanala; Fransiska Novita Sari (KHD-Production, 2022)
The older people with hypertension are one of the populations that have a susceptibility to COVID-19. Physical exercise activities are postponed, so the older people must adapt to this situation.This literature review aims to describe the physical exercise conditions of the older people with hypertension during the COVID-19 pandemic.The method used is a literature review by analyzing several relevant articles to answer the purpose of study. The online databases used are Science Direct, ProQuest, and Pubmed from 2019 to 2022. The keywords used to sort articles in this study are: (1) older people, (2) physical exercise, (3) hypertension, and (4) COVID-19. There were ten selected articles that analyzed. There are three main themes found in this literature review, namely (1) the types of physical exercise for the older people with hypertension during the COVID-19 pandemic, (2) the benefits of physical exercise for the older people with hypertension during the COVID-19 pandemic, and (3) the methods of carrying out physical exercise for the older people with hypertension during the COVID-19 pandemic. These results can be used as a basis for providing nursing care during to control blood pressure and quality of life of the older people with hypertension.